Relevansi Nilai-Nilai Sejarah Lokal dan Nasionalisme Generasi Muda - Jumardi jumardi12 (Jurnal Pendidikan Sejarah, 2020)
Local history has a role in building and strengthening nationalism and character in students. Local historical values ​​conveyed through daily actions, starting from the role of a person (figure), social culture (art, language and clothing) or historical events with a small narrative that exists in the neighborhood or educational environment where students are located. This study aims to provide an overview of the relevance of local history in life, so that it can become a provision in the next process, both as a member of the community or in the world of work. Studying local history will prevent students from being blind to history. The research method uses the survey method. Data obtained using observations and interviews with Uhamka students. The results of the study illustrate that more than 50% of students state that there is no relevance between local historical values ​​and nationalism. Students have not been able to interpret the events and values ​​of local history and nationalism, as well as the importance of mastering local history and its relation to national history. Sejarah lokal memiliki andil dalam membangun dan menguatkan rasa nasionalisme dan karakter pada mahasiswa. Nilai nilai sejarah lokal tersampaikan melalui tindakan sehari-hari, mulai dari peran seorang (ketokohan), sosial budaya (seni, bahasa dan pakaian) atau peristiwa sejarah dengan narasi kecil yang ada pada lingkungan tempat tinggal atau lingkungan pendidikan dimana mahasiswa berada. Penelitian ini bertujuan memberikan gambaran relevansi sejarah lokal dalam kehidupan, sehingga dapat menjadi bekal dalam proses selanjutnya, baik sebagai anggota masyarakat ataupun dalam dunia pekerjaan. Mempelajari sejarah lokal akan menghindarkan mahasiswa dari buta sejarah. Metode penelitian menggunakan metode survey. Data diperoleh menggunakan observasi dan wawancara terhadap mahasiswa Uhamka. Hasil penelitian menggambarkan lebih dari 50% mahasiswa menyatakan bahwa tidak ada relevansi antara nilai-nilai sejarah lokal dan nasionalisme. Mahasiswa belum dapat memaknai peristiwa dan nilai-nilai sejarah lokal dan nasionalisme, serta pentingnya penguasaan sejarah lokal dan kaitannya dengan sejarah nasional.